The Influence of Career Development and Organizational Commitment on Turnover Intention at PT Andalan Mutu Energi - Badriyah, Ratnaini; Retnowati, Ayu Nike; Pramayuda, Agung (CV ODIS, 2025)
This research aims to determine the description of Career Development, Organizational Commitment and Turnover Intention and to find the magnitude of the influence of Career Development and Organizational Commitment on Turnover Intention of PT Andalan Mutu Energi employees, both partially and simultaneously. The method used in this research is descriptive and verification with a quantitative approach. The population used in this research was all employees of PT Andalan Mutu Energi totaling 46 respondents using non-probability sampling techniques, namely saturated sampling techniques. Based on the results obtained, the respondents' description of Career Development and Turnover Intention is in the high category, Organizational Commitment is in the sufficient category. Based on the results of the determination test, it was found that Career Development had a 5.3% effect on Turnover Intention, Organizational Commitment had a 33.1% effect on Turnover Intention, Career Development and Organizational Commitment had a 40.3% effect on Turnover Intention. Based on the results of partial hypothesis testing, it shows that Career Development has a positive effect on Turnover Intention, Organizational Commitment has a negative effect on Turnover Intention. Based on the results of simultaneous hypothesis testing, Career Development and Organizational Commitment influence Turnover Intention.